Cardiac magnetic resonance in Fabry disease. (26th April 2023) - Lanzillo, Chiara; Fedele, Elisa; Martino, Annamaria; Ferrazza, Alessandro; Fusco, Armando; Silvetti, Elisa; Canestrelli, Stefano; Romeo, Fabiana; Canali, Emanuele; De Luca, Lucia; Golia, Paolo; Crescenzi, Cinzia; et al.
Abstract: Fabry disease (FD) is a rare X-linked inherited lysosomal storage disorder caused by deficient a-galactosidase A activity that leads to an accumulation of glycolipids, mainly globotriaosylceramide (Gb3) and globotriaosylsphingosine, in affected tissues, including the heart. Cardiovascular involvement usually manifests as left ventricular hypertrophy (LVH), myocardial fibrosis, heart failure, and arrhythmias, which limit the quality of life and represent the most common causes of death. Following the introduction of enzyme replacement therapy, early diagnosis and treatment have become essential in slowing down the disease progression and preventing major cardiac complications. Recent advances in the understanding of FD pathophysiology suggest that in addition to Gb3 accumulation, other mechanisms contribute to the development of cardiac damage. FD cardiomyopathy is characterized by an earlier stage of glycosphingolipid accumulation and a later one of hypertrophy. Morphological and functional aspects are not specific in the echocardiographic evaluation of Anderson–Fabry disease. Cardiac magnetic resonance with tissue characterization capability is an accurate technique for the differential diagnosis of LVH. Progress in imaging techniques has improved the diagnosis and staging of FD-related cardiac disease: a decreased myocardial T1 value is specific of FD. Late gadolinium enhancement is typical of the later stage of cardiac involvement but as in other cardiomyopathy is also valuable to predict the outcome and cardiac response to therapy.